Evaluation of Pesticide Use in Greenhouse Tomato Production in the Context of Sustainability, Food Safety and Export Residue Notifications - Hasan Yılmaz; Merve Mürüvvet Dağ (Journal of Agricultural Sciences)
The sustainability of agricultural production and access to healthy food are important issues in the agricultural sector. From a food safety perspective, pesticide residue problems are becoming an increasing concern for consumers worldwide. This study aims to evaluate pesticide use in greenhouse tomato production in terms of sustainability, food safety and export residue notifications. In this research, original data obtained from a face-to-face survey conducted with 115 greenhouse tomato farmers in Kumluca district of Antalya province was used. It was found that farmers on the surveyed farms used pesticides containing 57 different active ingredients. Various types of pesticides were used, including 12.9 kg/ha of insecticides, 10.9 kg/ha of nematicides, 8.8 kg/ha of fungicides, and 3.8 kg/ha of acaricides, resulting in a total of 36.5 kg/ha of pesticide use. The study revealed that 55.88% of the pesticides used by farmers were classified as hazardous according to the World Health Organization's (WHO) classification. The increasing number of pesticide residue notifications from European Union countries in recent years serves as a warning for Turkish farmers. Therefore, Türkiye needs to make more efforts to comply with international standards for the sustainability of tomato production and exports. As a result, in the research area, more efforts should be made to increase farmer training activities, tighten controls in greenhouse production, and strengthen safe food control mechanisms in order to reduce the use of pesticides for sustainable agriculture and safe food. In addition, greenhouse production support policies should be redesigned to encourage farmers to use biological control methods.